Visualizing Studies on Language Typology: A Bibliometric Analysis over 30 Years - Yang, Danlin (International Journal of Education and Humanities, 2024)
Language typology is a branch of linguistics that explores languages' classification and structural patterns, providing insights into their underlying ontological characteristics. Over the past few decades, this field has gained significant attention from the global academic community, driven by a growing interest in understanding linguistic diversity and universality. Despite its rapid development, a comprehensive analysis of research trends in this area remains limited. Therefore, this study aims to fill this gap by examining the evolution of language typology research from 1993 to January 2023. Utilizing the bibliometric tool CiteSpace, this study seeks to identify key research hotspots and emerging trends within the field. The research methodology involves a detailed bibliometric analysis, which allows for mapping scholarly publications and identifying significant contributions, collaborations, and citation networks. By analyzing data over 30 years, this study offers a longitudinal perspective on the progress and changes in the focus of language typology research. The findings reveal several notable trends, including a shift towards interdisciplinary approaches and the integrating of computational tools to analyze linguistic data. The research highlights emerging areas such as typological universals, linguistic complexity, and the interaction between language structure and cognition. Based on these results, the study recommends further exploration of under-researched languages and applying advanced computational techniques to deepen our understanding of typological patterns. Furthermore, it suggests fostering more international collaboration to address linguistic diversity across regions and language families. This study provides valuable insights for linguists interested in language typology research's current state and future directions